KINERJA PEMERINTAH DESA DALAM MEWUJUDKAN PELAYANAN PRIMA DI DESA GATTARENG KECAMATAN PUJANANTING KABUPATEN BARRU - Asisa, Nur; Burhanuddin, Burhanuddin; Akbar, Muhammad Randy (Universitas Muhammadiyah Makassar, 2025)
The purpose of this article is to assess the government's performance in delivering primary services in Gattareng Village, Pujananting District, Barru Regency, focusing on the performance of employees in service delivery. This study employs a qualitative research approach with a descriptive method. Data collection techniques include observation, interviews, and documentary studies. The researcher utilizes data analysis techniques involving data collection, data presentation, and drawing conclusions, with data validation through source triangulation, technique triangulation, and time triangulation. The findings of this study indicate that the performance of employees in providing primary services in the village is considered satisfactory; however, there is room for improvement, particularly in terms of punctuality and attendance issues. The government is advised to pay more attention to the tasks of employees and the needs of the community as a whole.